Association of Serum Uric Acid and Hypertension among Hypertensive Patients in Local Community - Hayee, Pir Abdul; Memon, Khalil Ahmed; Khan, Muhammad; Samad, Abdul; Attaullah,; Ansari, Shafaq (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To analyze the association of hypertension and serum uric acid levels among hypertensive subjects in local community of Mirpurkhas Study Design: Descriptive non interventional study Place and Duration of Study: Various Clinical Setups of Mirpurkhas, Sindh, Pakistan from 1st July 2021 to 31st December 2021. Methodology: Four hundred and seventeen patients were recruited via rao-soft formula based on confirmed diagnosis of hypertension irrespective of age and gender. A serum uric acid was also measured. Results: Two hundred and sixty nine (64.5%) were males and 148 (35.5%) were females. There were 117 (28.05%) had age from 55-65 years and 132 (31.65%) had more than 6 years. Moreover in male gender 73 (27.18%) had uric acid value from 9.1 to 10 mg/dL while in female 37 (25%) had uric acid value from 8.1 to 9 mg/dL. Conclusion: Male gender was more prone towards hypertension and uric acid abnormal values. Mainly the adult patients were more affected having age more than 55 years and had chronic hypertension. Further it was revealed that uric acid values found high in hypertensive patients in both genders i.e. male and female. The values were of more than 8 mg/dL. Proper diagnosis will be the integral part to diagnose the patients particularly in chronic problems.